The Role of Parents in Reducing Online Gaming Addiction Among Students of SMP Negeri 11 Medan - Amin, Afriadi; Batubara, Abdul Karim; Budiman, Budiman; Damayanti, Purba Eka; Suyono, Hanny Chairany (Faculty of Law, Universitas Pekalongan, 2024)
The research is entitled The Role of Parents in Reducing Online Game Addiction in Students of SMP Negeri 11 Medan. The formulation of the problem in this study is how the role of parents in reducing online game addiction, how the impact of online game addiction and what are the factors that become obstacles for parents in reducing online game addiction in students of SMP Negeri 11 Medan. The research aims to find out the role of parents in reducing online game addiction, knowing the impact of addiction and knowing the factors that become obstacles for parents in reducing online game addiction in students of SMP Negeri 11 Medan. This research uses a descriptive method with a qualitative approach where this research uses Miles and Huberman data analysis techniques. The results of this study indicate that the role of parents is very important for the growth of children, therefore parents must do several things so that children are not addicted to gadgets and online games including: by mentoring, supervision and open communication. Efforts to avoid the use of gadgets and online games in it are by the way each parent must take several actions or preventive measures to minimize the use of cell phones in children, by limiting time, making commitments from the beginning with children so that in children there will be a sense of responsibility and think they have a promise with their parents that they should not break. It can be concluded that the factors that influence online gaming are the frequency of playing online games, the time of playing online games, and the games or games that are favored.